Effect of a novel sternal recumbency approach for quadratus lumborum block on isoflurane requirements in cats undergoing ovariohysterectomy - Takusagawa, Fumihiko; Takusagawa, Yoshimi; Kimura, Taro (Frontiers in Veterinary Science, 2025)
IntroductionThis prospective, randomized clinical study with a sequential design aimed to evaluate whether a novel quadratus lumborum block (QLB) technique applied in sternal recumbency could reduce isoflurane requirements and enhance procedural safety in cats undergoing ovariohysterectomy.MethodsThirty-five American Society of Anesthesiologists physical status (ASA-PS) I female cats, either client-owned or sheltered, undergoing ovariohysterectomy. Cats were randomly assigned to different groups to undergo either conventional QLB technique in lateral recumbency (CQLB group, n = 17) or novel QLB technique in sternal recumbency (NQLB group, n = 18). Ultrasound-guided injections were performed bilaterally, targeting the fascial plane between the quadratus lumborum and psoas minor muscles, with 0.4 mL kg−1 bupivacaine administered per side. Cats were premedicated with dexmedetomidine, anesthetized with propofol and isoflurane. The end-tidal isoflurane concentration (ETiso) was adjusted based on heart rate (HR), respiratory rate, and mean arterial pressure (MAP). Outcomes included total mean ETiso, phase-specific ETiso, total mean HR and MAP, rate of needle proximity to abdominal organs, rates of bradycardia, hypotension, and the need for postoperative analgesics, assessed using both the Short-form UNESP-Botucatu Multidimensional Composite Pain Scale and the Feline Grimace Scale.ResultsCats in the NQLB group demonstrated slightly lower total mean ETiso (p = 0.046) and significantly reduced ETiso during right ovariectomy (p = 0.022) and hysterectomy (p = 0.007) compared with cats in the CQLB group. Total mean HR and MAP did not differ between groups. Needle proximity to abdominal organs was observed in all CQLB cats but not in any NQLB cats. No bradycardia or hypotension was observed. There was no significant difference in the requirement for postoperative rescue analgesic between the groups.DiscussionThe novel QLB technique demonstrated a superior isoflurane-sparing effect and safety compared with that of conventional QLB in cats. This approach may benefit cats undergoing ovariohysterectomy.